Childhood and Army. The Story of Army Cadet Children at the Eloy Alfaro Military School in Quito, Ecuador, 1969 – 1972 (2018)
After five decades, the memory of fifty-five children is recovered. Once they entered the Eloy Alfaro Military School in 1969, they inaugurated the secondary education that was only offered from the fourth grade at the Military School, specifically intended for the training of Ecuadorian Army officers. Since a large extent of this work was built on interviews, we were able to reveal the experiences of three years of illusions, sacrifices, pranks, abuse, and new knowledge of those cadet children who started the first course under the mantle of a patriotism feeling, and other civic beliefs, that should be forged in them. This testimonial research was carried out in the city of Quito. The sample consisted of a group of six officers of the Ecuadorian Army who starred in this story. The financing was never an obstacle because the interview was one of the primary sources.